Oral sensory and cephalic hormonal responses to fat and nonfat liquids in bulimia nervosa - Bello, Nicholas T. (2010)
Sensory evaluation of food involves endogenous opioid mechanisms. Bulimics typically limit their food choices to low fat “safe foods” and intermittently lose control and binge on high fat “risk foods”. The aim of this study was to determine whether the oral sensory effects of a fat versus a non-fat milk product (i.e., traditional versus non-fat half-and-half) resulted in different subjective and hormonal responses in bulimic women (n=10) compared with healthy women (n=11). Naltrexone (50 mg PO) or placebo was administered 1 h before, and blood sampling began 30 min prior to and 29 min after, a 3 min portion controlled modified sham-feeding trial. Following an overnight fast, three morning trials (Fat, Naltrexone; Fat, Placebo; and Non-Fat, Placebo) were administered in a random double-blind fashion separated by at least 3 days. Overall, there were no differences between Fat and Non-Fat trials. Hunger ratings (p<0.001) and pancreatic polypeptide levels (p<0.05) were higher for bulimics at baseline. Bulimics also had overall higher ratings for nausea (P<0.05), fatty taste (P<0.01), and fear of swallowing (P<0.005). Bulimics had ∼40% higher total ghrelin levels at all time points (P<0.001). Hormones and glucose levels were not altered by the modified sham-feeding paradigm. Naltrexone, however, resulted in an overall increase in blood glucose and decrease in ghrelin levels in both groups (P<0.05, for both). These data suggest bulimic women have different orosensory responses that are not influenced by opioid receptor antagonism, evident in hormonal responses, or dependent on the fat content of a similarly textured liquid.